A importância do bloqueio continental para o futuro de Portugal e do Brasil - Ribeiro, Jorge Martins (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The Continental Blockade, declared by Napoleon Bonaparte in November 1806, had huge repercussions in the shaping of Portugal and Brazil’s political future. Lisbon’s refusal to close its national ports to commerce with the British prompted France to invade Portugal for three times, from 1807 to 1811. These invasions not only had devastating consequences in the country’s economy and society, but also affected the political and social events following the collapse of Napoleon’s empire. At the same time, the transfer of the Portuguese court to Brazil was decisive for the colony’s future, culminating in the declaration of independence in 1822, which leads some historians to consider King John VI of Portugal the “founder of the Brazilian nationality”.